1999
DOI: 10.1080/07448489909595660
|View full text |Cite
|
Sign up to set email alerts
|

Combating Sexual Offenses on the College Campus: Keys to Success

Abstract: The authors emphasize the need for programs to prevent sexual offenses at institutions of higher education. They briefly describe efforts underway at Bowling Green State University and offer 6 strategies for improving the likelihood of success in sexual assault education, prevention, and response efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Factors that may increase the likelihood of assaults (eg, use of drugs or alcohol) and strategies to prevent sexual assaults (eg, "buddying up, " not drinking from a vessel that has been left unattended, abstaining from or moderating alcohol intake, and not accepting drinks from strangers) can be discussed, and associated educational materials can be made available and distributed by pediatricians, particularly during the adolescent years and at the precollege visit. [134][135][136] College health professionals, including physicians, nurses, and health educators, along with specialists in student services/ student affairs, can also work with at-risk communities in university settings (eg, athletics, housing, freshmen organizations, Greek life) to provide education and resources to reduce the risks of sexual violence on and beyond campus.…”
Section: Sexual Assault Preventionmentioning
confidence: 99%
“…Factors that may increase the likelihood of assaults (eg, use of drugs or alcohol) and strategies to prevent sexual assaults (eg, "buddying up, " not drinking from a vessel that has been left unattended, abstaining from or moderating alcohol intake, and not accepting drinks from strangers) can be discussed, and associated educational materials can be made available and distributed by pediatricians, particularly during the adolescent years and at the precollege visit. [134][135][136] College health professionals, including physicians, nurses, and health educators, along with specialists in student services/ student affairs, can also work with at-risk communities in university settings (eg, athletics, housing, freshmen organizations, Greek life) to provide education and resources to reduce the risks of sexual violence on and beyond campus.…”
Section: Sexual Assault Preventionmentioning
confidence: 99%
“…Through a team approach, involving such resources as health and psychological services, the offices of student life, residential life, and multicultural affairs, the campus police, and the athletic department, a number of universities have successfully developed and implemented sexual assault prevention policies which have led to increased reporting of sexual assaults and improved uptake of appropriate resources for victims. 16,17 A widespread team approach, furthermore, allows for sexual assault prevention initiatives to be viewed as a concern to the entire university and not a specific interested group. For example, at the start of the fall semester at Southern Illinois University, group presentations, including videotapes on the topic of date rape followed by a discussion led by student affairs personnel, are required.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that may increase the likelihood of assaults (eg, use of drugs or alcohol) and strategies to prevent sexual assaults (eg, "buddying up," not drinking from anything that has been left unattended, abstaining from or moderating alcohol intake, not accepting drinks from strangers) should be discussed, and associated educational materials should be available and distributed. 47,70,[91][92][93] A survey of more than 600 young women in an urban setting showed that the vast majority thought that young women should be screened and counseled by their health care professional regarding dating violence. 94 Physicians should be aware that sexual assault is common and need to be prepared to counsel their adolescent patients to avoid high-risk situations.…”
Section: Sexual Assault and Rape-prevention Strategiesmentioning
confidence: 99%
“…Prevention messages for adolescents need to be designed for males and females. 47,70,[91][92][93] Adolescents need to be able to identify high-risk situations (such as attending parties with unknown people, meeting people with whom they have had contact on the Internet, walking alone at night, allowing themselves to be photographed nude or in sexually explicit poses or situations); they also should be advised that if they are ever assaulted, they should seek medical care. Factors that may increase the likelihood of assaults (eg, use of drugs or alcohol) and strategies to prevent sexual assaults (eg, "buddying up," not drinking from anything that has been left unattended, abstaining from or moderating alcohol intake, not accepting drinks from strangers) should be discussed, and associated educational materials should be available and distributed.…”
Section: Sexual Assault and Rape-prevention Strategiesmentioning
confidence: 99%